PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP KINERJA KEUANGAN BANK MANDIRI - Rukma Kalista, Widiani; Susilo (Contemporary Studies in Economic, Finance and Banking, 2024)
This research aims to determine the influence of internal (CAR, BOPO and NPL) and external factors (Inflation, Interest Rates and Economic Growth) on Bank Mandiri financial performance. In this research, financial performance is measured by ROA. The method used in this research is the multiple linear regression method. The data used is secondary data in the form of a time series with a time period from 2012 Q1 – 2021 Q4. The results of this research show that the BOPO and Interest Rate variables have a significant effect on Bank Mandiri financial performance. Meanwhile, the CAR, NPL, Inflation and Economic Growth variables do not have a significant effect on Bank Mandiri financial performance.